ANALISIS PENGARUH BRAND EVALUATION, BRAND TRUST, DAN BRAND SATISFACTION TERHADAP BRAND LOYALTY MELALUI BRAND RELATIONSHIP - Ibadi, Iman khusni; Indriani, Farida (Diponegoro Journal of Management, 2017)
Based on research conducted by Veloutsou (2015) on the cosmetics industry, especially lipstick users in the city of Glasgow show that brand evaluation, brand trust, and brand satisfaction have a positive and significant effect on brand loyalty through brand relationship as intervening variable. Although the research contributes significantly to the impact of brand evaluation, brand trust, and brand satisfaction on brand loyalty through brand relationships, it is still limited to the cosmetic industry context that is open to similar research in different industry contexts. This research aims to find the influence of brand evaluation, brand trust, and brand satisfaction on brand loyalty through brand relationship as intervening variable. The study was conducted on consumers of Telkomsel who live in Semarang city that a minimum purchase at least one year before. The sampling method used non-probability purposive sampling. The data was collected through questionnaires. The samples used in this study was 100 respondents. Then the data processed using analytical techniques a multiple regression analysis and sobel test. The result showed that brand relationship as intervening variable, mediate influence of brand evaluation, brand trust, and brand satisfaction on brand loyalty.